Lignin nanofiller-reinforced composites hydrogels with long-lasting adhesiveness, toughness, excellent self-healing, conducting, ultraviolet-blocking and antibacterial properties. (15th November 2021) - Cui, Han; Jiang, Weikun; Wang, Chao; Ji, Xingxiang; Liu, Yu; Yang, Guihua; Chen, Jiachuan; Lyu, Gaojin; Ni, Yonghao
Abstract: Multifunctional hydrogels have drawn much attention as functionalized materials, and the composites hydrogel concept is an effective approach to fabricate hydrogels that simultaneously possess multiple functions, such as long-lasting adhesiveness, toughness, excellent self-healing, conducting, ultraviolet-blocking and antibacterial properties. In this work, such hydrogels were fabricated by using functionalized lignin nanoparticles (LNP) as fillers in hydrogel preparation. In the first step, lignin nanoparticles with narrow size distribution of 250–350 nm were prepared, and subsequently decorated with Ag nanoparticles (∼10 nm) on their surface. During the gelation process, the use of LNP@Ag, Fe 3+, ammonium persulfate (APS) and acrylic acid (AA) led to an ultrafast PAA polymerization at ambient temperature (in only a few minutes). Furthermore, due to the dynamic catechol redox-Fe 3+ system, the LNP@Ag–Fe 3+ containing hydrogel exhibited excellent mechanical properties, particularly exceptional durability, and displayed long-term adhesiveness, and rapid and efficient self-healing ability. As nanofillers, LNP@Ag further strengthened the hydrogels, with excellent compression strength of ∼810 kPa and elasticity (stretching to 13 times its initial length). In addition, the composites hydrogel possessed excellent conductivity, ultraviolet-blocking properties, and high antibacterial activity due to the presence of metal ions, lignin, and Ag nanoparticles. This study provides a new strategy of using lignin nanofillers for the fabrication of hydrogels, and this easy-to-prepare and multifunctional hydrogel shows promising applications in human-machine electronics. Highlights: Novel LNP@Ag nanofillers were fabricated for applications in multifunctional hydrogel preparation. LNP@Ag nanofillers have multiple functions: radical initiator, reinforcing nanofillers, reducing, antibacterial and UV-blocking agent. Multifunctional hydrogels show promising applications in human–machine electronics.